REPRODUCTION ASPECTS OF THE YELLOWFIN TUNA (Thunnus albacares) - Retno Andamari; Jhon Haryanto Hutapea; Budi Iskandar Prisantoso (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2012)
Tuna is one of the important fishery commodities in Indonesia, including tuna caught by longliners in Indian Ocean. The most popular of tuna is yellowfin tuna (Thunnus albacares). Currently, the production of tuna based on the capture fisheries, therefore, in order to preserve its sustainability, the understanding of the biological and reproduction aspect is required. Research on the biological reproduction of this species was conducted at Gondol Research Institute for Mariculture. Samples of female gonad were collected from Indian Ocean tuna longliners during April to July 2009 from the processing companies within Benoa Port. Result of the histological analysis on 128 female gonads showed that majority of gonads were at the early development level and the only 16 gonads have reached at the mature level. The analysis of the oocyte development showed the asynchronous, indicating that yellowfin tuna is a multiple spawner.Keywords: yellowfin tuna, gonad, asynchronous